A narrative review on the effectiveness of therapeutic communication in reducing anxiety in children during dental treatment procedures - Ridho, Fiki Muhammad; Fauzan, Moh. (International Journal of Health, 2023)
Background: Dental anxiety is anxiety about dental treatment carried out before or immediately after a dental treatment procedure, which will have an impact on the difficulty of the dental team in carrying out dental treatment. One of the interventions that the dental team can carry out with pediatric patients is therapeutic communication.Objective: This study aims to further discuss regarding the effectiveness of therapeutic communication in reducing anxiety in children during dental treatment procedures.Methods: A systematic search of the Google Scholar database, then a narrative review of the identified articles was conducted with a focus on articles published in the last 10 years.Discussion: Therapeutic communication, a non-pharmacological intervention, plays an important role in managing anxiety in children when undergoing dental treatment procedures, because it has the benefit of reducing psychological problems in children such as anxiety, fear and changes in behavior, especially during dental treatment procedures. Some scientific evidence shows a significant value of p <0.05 and an OR value >1 which indicates a correlation between therapeutic communication and the level of dental anxiety.Conclusion: Based on the results of the narrative review conducted, we conclude that the better the therapeutic communication carried out by the dental team, the lower the level of anxiety in children during dental treatment procedures.